A necessary evil? The rise of online exam proctoring in Australian universities. Issue 1 (February 2023) - Selwyn, Neil; O'Neill, Chris; Smith, Gavin; Andrejevic, Mark; Gu, Xin
The COVID-19 pandemic has seen the rapid but sometimes controversial take-up of 'online examination proctoring' systems by universities keen to maintain their assessment schedules during times of campus closure. Following the theoretical tradition of media 'domestication', this article examines the mainstream adoption of different online proctoring systems in Australian higher education during the first year of the pandemic. Through analysis of interviews, documents, news, social media and marketing materials, the article examines the 'appropriation', 'objectification', incorporation' and 'conversion' of proctoring technology from the perspective of commercial providers, university authorities, university staff and student groups. This raises a number of critical issues underpinning the adoption of this exam surveillance technology – not least the surrender of control to commercial providers, the hidden labour required to sustain 'automated' systems and the increased vulnerabilities of 'remote' studying.